Antecedents of Customer Purchase Intention of Fashion Products Among Millennials and Z Generation Using Multi-Group Analysis - Pasaribu, Romindo M; Simanjuntak, Juara; Simanjuntak, Agus Nakkok (Universitas Pendidikan Nasional, 2025)
This study aims to examine the variable of customer engagement in mediating the relationship between omnichannel integration quality and the purchase intention of Millennial and Gen Z customers for fashion products. The study involved a sample size of 145 respondents, employing a nonprobability sampling method using purposive sampling. Data analysis was conducted using the Partial Least Squares (PLS) method with SmartPLS. The findings indicate that the configuration of service channels and integrated interactions positively and significantly affect customer engagement and purchase intention for both generations. However, the multi-group analysis revealed that while the configuration of service channels, integrated interactions, and quality assurance positively influence customer engagement and purchase intention among Millennials, these effects are not statistically significant. For Generation Z, the configuration of service channels and integrated interactions significantly influence customer engagement and purchase intention. In contrast, quality assurance does not significantly impact customer engagement or purchase intent for either generation. Customer engagement serves as a mediator between the configuration of service channels and integrated interactions on purchase intent for Generation Z, but it does not act as a mediator for Millennials. Additionally, customer engagement cannot mediate the impact of quality assurance on purchase intent for either generation in Medan when shopping for fashion products through an omnichannel approach. Retailers are encouraged to enhance shopping engagement for Millennials and Generation Z by offering multiple shopping channels, including various accounts on each platform and e-commerce site.